Mobilität im Wandel. Wie der Klimaschutz den Transportsektor vor neue Herausforderungen stellt. - Creutzig, Felix; Edenhofer, Ottmar (Deutscher Verkehrs-Verl., 2010)
Der Intergovernmental Panel on Climate Change (IPCC) empfiehlt eine weltweite Reduktion der Treibhausgasemission von mindestens 50 % bis 2050, um gefährlichen Klimawandel zu vermeiden. Von einer nachhaltigen Senkung der Emissionen ist die Weltwirtschaft jedoch trotz der Finanzkrise noch weit entfernt. Derzeit steigen die Emissionen nämlich weltweit - im Transportsektor sogar schneller als in anderen Sektoren. Eine Vermeidung gefährlichen Klimawandels wird daher nur möglich sein, wenn die Emissionen im Transportsektor weit unter das heutige Niveau abgesenkt werden.

A significant contribution of the transport sector is required to achieve ambitious reduction of greenhouse gas emissions until 2050. In the article, we summarize findings on the emissions within the transport sector, highlighting underlying factors of two important world regions, the U.S. and China. We then take a closer look at energy system models, and predictions of how the transport sector can decarbonize cost-effectively. A more detailed excursion focuses on the importance of accurate life-cycle analysis of novel fuels. In the last part, we explore a number of policy instruments, specifically those geared to the carbon content of fuels. We suggest a possible evolution of renewable fuel standards, to low carbon fuel standards and finally to an economic-wide cap and trade system. We close by describing two policies, fuel efficiency standards and infrastructure investments, that are of particular importance to our p revious case studies, the U.S. and China.
Mobility in change.
Keywords: Verkehr; Emission; Umweltpolitik; Energiepolitik; Mobilität; Transport; Güterverkehr; Verkehrsverhalten; Verkehrsnachfrage; Klima; Wirkung; Treibhausgas; Klimawandel; Verkehrssektor; Emissionsminderung; Klimapolitik; Emissionshandel; Energieeffizienz